Respuesta :

Tasyha

Answer:

D. -1.44 and 2.44

Step-by-step explanation:

[tex]f(x) = 2 {ax}^{2} + (3 - b)x + 7[/tex]

is equal to:

[tex]g(x) = (a - 1) {x}^{2} + 2bx + 7[/tex]

•◇•◇○◇•◇•

➡️ [tex] - 2 {x}^{2} + 2x + 7 = 0[/tex]

➡️ [tex]Δ = {b}^{2} - 4ac = 4 - 4 \times 7 \times ( - 2) = 60 = \sqrt{Δ} = 7.746[/tex]

➡️ [tex]x = \frac{ - b± \sqrt{Δ} }{2a} = \frac{ - 2± 7.746}{ - Δ} [/tex]

➡️ [tex] x_{1} = \frac{ - 2 + 7.746}{ - 4} = - 1.44[/tex]

➡️ [tex] x_{2} = \frac{ - 2 - 7.746}{ - 4} = 2.44[/tex]

ACCESS MORE